Plasma Ip(a) concentration is inversely correlated with the ratio of Kringle IV/Kringle V encoding domains in the apo(a) gene. - Gavish, D; Azrolan, N; Breslow, J L (The Journal of Clinical Investigation, 1989)
Plasma Lp(a) levels correlate with atherosclerosis susceptibility. This lipoprotein consists of an LDL-like particle attached to a large glycoprotein called apo(a). Apo(a) is a complex glycoprotein containing multiple Kringle domains, found to be highly homologous to plasminogen Kringle IV, and a single Kringle domain homologous to plasminogen Kringle V. Lp(a) levels appear to be inversely correlated with apo(a) size in a given individual. In this study, we have used probes specific to the Kringles IV and V domains of apo(a) cDNA in quantitative Southern blotting analysis. By this method, we have determined the ratio of Kringle IV/Kringle V encoding domains in the apo(a) gene of 53 unrelated individuals with different plasma concentrations of Lp(a). This ratio was found to be inversely correlated with log Lp(a) levels (r = -0.90, P less than 0.0001) and directly correlated with apo(a) apparent molecular weight (Mr) (r = 0.79, P less than 0.0001). In summary, by showing that Lp(a) concentrations and apo(a) apparent size are highly correlated with the ratio of Kringle IV/Kringle V encoding domains in the apo(a) gene, we provide a DNA marker for this atherosclerosis risk factor as well as an important insight into the genetic mechanism regulating Lp(a) levels. Images